Thermal evolution of the lithosphere beneath the French Massif Central as deduced from geothermobarometry on mantle xenoliths - Werling, Friederike; Altherr, Rainer (Tectonophysics, 1997)
The chemical compositions of minerals in mantle xenoliths from Miocene-Holocene volcanic rocks have been used to model the thermal evolution of the lithospheric mantle beneath the French Massif Central. Reequilibration of mineral compositions after entrainment in melts and during ascent to the surface was generally weak as documented by Ca zoning patterns of olivine grains. About half of the 73 xenoliths studied are characterized by significant intra-grain compositional variations reflecting chemical disequilibrium and partial reequilibration under changing thermal conditions prior to their entrainment in melts. Different types of Al and Ca zoning patterns of pyroxene grains are interpreted in terms of simple heating, simple cooling and two-stage thermal evolutions with early cooling followed by later heating. Diffusion modelling yields durations of several ka to less than a few Ma for these thermal events. Thermobarometric (P-T) data on 40 equilibrated xenoliths with more or less homogeneous mineral compositions plot along and above a 90 mW m−2 model steady-state geotherm with equilibration temperatures ranging from about 700 to 1280°C. Miocene and Pliocene-Holocene xenoliths define roughly similar P-T data arrays. Extrapolation of these arrays to the adiabatic upwelling curve of normal temperature asthenosphere results in an apparent lithospheric thickness of 70-80 km. These findings are in line with surface heat flow data and the results of seismic tomography.